Integrasi Higinitas, Sanitasi, dan Nilai-Nilai Religius di Lingkungan Pesantren - Noer Aisyah Barlian; Guntur Kusuma Wardana; Wahyuning Murniati (Lembaga Pengembangan Kinerja Dosen, 2024)
Pesantren, as the oldest Islamic educational institutions, face complex challenges in environmental health management, primarily due to high residential density, limited sanitation infrastructure, and varying practices of Healthy and Clean Living Behaviors (PHBS). Although the religious concept of taharah (purity) serves as a foundation for cleanliness, there is a lack of in-depth research examining the integration of religious values, infrastructure conditions, and management systems in shaping the daily hygiene experiences of santri (students).This study aims to explore the santri's experience regarding environmental health management in pesantren, focusing on the integration of hygiene, sanitation, and Islamic religious values, while also identifying factors and challenges related to PHBS practices. This qualitative research, utilizing a descriptive phenomenology design, collected data through in-depth interviews with three female santri informants (with 8–9 years of boarding experience). Data analysis was conducted using the six-phase thematic analysis method by Braun & Clarke (2006).The study identified five main themes: (1) Infrastructure is quantitatively adequate but faces operational issues (queues, seasonal clean water scarcity); (2) PHBS practices show positive behavioral changes (self-reliance) but waste management remains traditional; (3) The religious value of taharah acts as a strong intrinsic motivation; (4) The management system involves multi-level roles (kiai-ustaz-administrators) that face consistency challenges; and (5) Main obstacles include limited facilities, varying levels of santri awareness, and disparity in educational programs. Poskestren (Pesantren Health Post) represents an institutional effort to provide basic health services.Environmental health management in pesantren requires a holistic approach, integrating infrastructure improvement and sustainable waste management systems, alongside developing education that unites Islamic religious values with modern health knowledge. Optimizing the religious strategy and strengthening national monitoring/standardization systems are key to program sustainability.